The Role of Management Information Systems in the Healthcare Industry in E-Health and E-Hospital Programs - Dewi Puspaningtyas Faeni; Nabila Zahra Octaviany (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the role of management information systems in the health industry in e-health and e-hospital programs. In the era of globalization, technological developments have had an impact on business progress, including the health industry. E-health and e-hospital as one of the internet-based technology applications require strategies to improve business efficiency and productivity. This study uses a qualitative method with a descriptive approach and a literature study method. The results of the study indicate that E-Health and E-Hospital services can make it easier for people to access health services easily and efficiently. It is hoped that in the future it can provide more complete services, such as adding several Hospitals and Health Centers to its website, giving customers access to the various Hospitals they need.